Educational Thought of Islamic Philosophers Perspective of Islamic Philosophy of Education - Busthomi , Yazidul; Alivi , Justsinta Sindi; Haris , Abd (Al-Insyiroh: Jurnal Studi Keislaman, 2024)
The true goal of education is to increase human competency, which is achieved through the application of different information and skills that humans themselves require. The goal of education is to support students' human potential development. Education is seen by Indonesians as the country's battle. History has demonstrated that ties and exchanges with the Islamic civilization, which is presently undergoing growth, are inextricably linked to the highs and lows of education. With the rise of Islamic education ideas, this is undeniable. History reveals that the Abbasid period, which reached its zenith, is when Islamic educational philosophy started to take shape. The idea of education, which includes children's education, educational objectives, and educational principles, was first articulated by Al-Qabisi.It is impossible to learn about other objects that have a higher ontological status, namely immaterial reality, without the presence of the five senses, according to Ikhwan As-Shafa. Only the five senses are capable of perceiving objects in the form of material-physical reality that are present in space and time. metaphysical. The As-Shafa Brotherhood's profound admiration of the senses demonstrates the significant influence of Aristotelianism in their epistemological thought. In this regard, they even venture to promise that, provided all circumstances are met, there will be no errors made by the senses.